Vida Saludable: Derrumbando Barreras en Contra de la Actividad Física - Jennifer Hillan (EDIS)
FCS8818-Span, a 2-page fact sheet by Jennifer Hillan, is the Spanish version of "Beating Barriers to Physical Activity" (FCS8818/FY883). It reminds older adults of the importance of regular physical exercise and provides suggestions for handling some common problems and issues that keep people from exercising. Published by the UF Department of Family, Youth and Community Sciences, December 2006.